Noise Impact of Southgate Phase-2 Construction Project to the Settlement at Perumahan Tanjung Mas, Tanjung Barat - Askarini Sekar Putri (Applied Research on Civil Engineering and Environment (ARCEE), 2021)
Construction activities can increase noise that gives an impact on the people who live nearby. The impact of noise can cause psychological and physiological disorders. The purpose of this research is to analyze the effects of the noise level of the Southgate Phase-2 project for citizen activities at PerumahanTanjung Mas, Tanjung Barat. It is based on regulatory standards in KEPMEN LH no. 48 of 1996, KEPGUB DKI Jakarta no. 551 of 2001, and the LNP standard according to the US Department of Housing and Urban Development. The methods are doing observation and survey by using a questionnaire to find out the project situation and the noise level produced by using a sound level meter measuring instrument. The result shows that people feel discomfort from the noise of the project, especially at night. Most of the noise measurement result exceeds the noise quality standard and its effects up to 50 meters away from the noise source. The point which is about 5 meters away from the noise source is 63.73 dB (A) and point which is about 50 meters away from the noise source is 59.89 dB (A). Based on the results of the regression equation shows that houses within 120 meters of the project impacted by the noise that exceeds the noise quality standards for the residential area. The most complaints given by people of PerumahanTanjung Mas were feeling discomfort in daily activities (79%), and sleeping trouble (60%).